Penerapan Metode Six Sigma Dalam Pengendalian Kualitas Produk E-Clip Railway Di Perusahaan Foundry - Iis Nafisa; Bayu Wiro Karuniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
A metal foundry company is producing e-clip. Based on 2021 data, e-clip products have 13 types of defects. Miss run being one of these defects which are included in the category that cannot be repaired with a percentage of 15.16%. This study aims to determine the factors that cause defects in e-clip products. The method used is Six sigma DMAIC. The measuring stage obtained 4.1 sigmas from the DPMO calculation. In the analysis stage using FTA obtained 7 factors, namely the operator is inconsistent during the pouring process, the inoculation process is less precise, the tapping temperature check is not carried out regularly, transfer speed from tapping to moulding is too long, the content water in the molding is too much, the ladle rinsing temperature is not high, the molding line does not stop when the operator is doing the pouring process.